Globalisation and Pace of Economic Growth in Nepal (Voice: A Biannual & Bilingual Journal, 2023)
Nepal faced serious economic crisis during mid 1980s. Overall balance of payment of the country turned negative in 1982/83 and it remained in the same pattern for three consecutive years. Nepal approached the IMF and the World Bank for their support in solving the economic crises that were being experienced at that time. In response to Nepal's approach these institutions helped Nepal with financial assistance with conditions in order to tide over the external imbalance. These institutions made reformation policies and Nepal had to implement these policies. Nepal entered into the new era of international economic order termed as 'Globalisation'. Nepal formulated and implemented many economic reformation policies compatible with the process of globalisation, liberalisation and privatisation in order to accelerate the process of economic globalisation. This paper aims at studying and analyzing effects of globalisation of Nepalese economy on GDP growth rate and its composition during last three decades starting from 1991/92. The study finds that the globalisation of Nepalese economy has not been able to accelerate the pace of economic growth at desired level.